ANALYSIS OF THE EFFECT OF ENTRY PATHWAYS ON STUDENT ACADEMIC ACHIEVEMENT AT UIN SUNAN GUNUNG DJATI BANDUNG: A STUDY ON THE CLASS OF 2022 AND 2023 - Tedi Priatna; Muhammad Amar Khana (Khazanah Multidisiplin, 2024)
This study aims to analyse the influence of admission pathways (SPAN PTKIN, UM PTKIN, and Independent) on students' academic performance at UIN Sunan Gunung Djati Bandung for the 2022 and 2023 cohorts. The research evaluates academic indicators such as GPA, credits taken, participation in seminars, and organisational involvement. Using a mixed-method design, quantitative data were collected through a questionnaire distributed to 560 students. Data were analysed with ANOVA and post hoc Games-Howell tests, while qualitative data explored students’ perceptions. Results indicate no significant differences in GPA, credits taken, seminar participation, or organisational involvement among students from different admission pathways. However, significant differences were found in the intensity of the study between UM-PTKIN and independent pathways. These findings suggest that UIN Sunan Gunung Djati Bandung has successfully implemented an inclusive education system, ensuring equal opportunities for all students regardless of their admission pathway. This study provides a comprehensive analysis of the impact of admission pathways on student performance at PTKIN, contributing to the discourse on higher education inclusivity in Indonesia.